Objectively assessed physical activity patterns and physical function in community-dwelling older adults: a cross-sectional study in Taiwan - Yung Liao; Ming-Chun Hsueh; Ru Rutherford; Chien-Chih Chou; Jong-Hwan Park; Hyun-Tae Park (BMJ Open)
Objectives To objectively assess light physical activity (PA), moderate-to-vigorous PA (MVPA), step counts and number of 10 min MVPA bouts and their association with physical function among older adults.Design Cross-sectional design.Setting Urban community setting in Taiwan.Participants 127 Taiwanese older adults aged over 65 years (mean age=70.8±5.3 years; 72% women).Primary and secondary outcome measures Triaxial accelerometers were used to measure PA variables for 10 hours/day for seven consecutive days. Then, five physical function components (handgrip strength, single-leg stance, 5-metre walk speed, timed up and go and sit-to-stand test) were measured. Multiple linear regressions were used to perform separate analyses for older men and women.Results For older women, daily MVPA time (β: 0.39, 95% CI: 0.12, 0.64; p=0.004), daily step counts (β: 0.46, 95% CI: 0.12, 0.78; p=0.009) and number of 10 min MVPA bouts (β: 0.27, 95% CI: 0.001, 0.53; p=0.049) were positively associated with handgrip strength after adjusting for accelerometer wear time, sedentary time and other confounders. Furthermore, daily MVPA time was positively associated with a single-leg stance (β: 0.25, 95% CI: 0.02, 0.49; p=0.036) and higher daily step counts were associated with shorter walking speed performance (β: −0.31, 95% CI: −0.57, −0.001; p=0.049). None of the variables of the objectively assessed PA patterns was associated with physical function outcomes among older men due to their small sample size.Conclusions Daily MVPA, MVPA bouts of at least 10 min and accumulated daily steps are important for improving physical function among older women. Future prospective research should establish causal associations between PA patterns and functional ability among older adults.